Patterns, Outcomes and Predictors of Pediatric Medical Admissions at Gadarif Hospital in Eastern Sudan - Ahmed, Mohammed Ahmed A.; Musa, Imad R.; Mahgoub, Hyder M.; Al-Nafeesah, Abdullah; Al-Wutayd, Osama; Adam, Ishag (Frontiers in Pediatrics, 2022)
Background: The reduction of childhood mortality is a reliable indicator of a national health system’s progress and improvement. Sudan’s population is still suffering from communicable diseases, with a considerably higher mortality rate among children. Efforts are therefore needed to reduce mortality and achieve the Millennium Development Goals and Sustainable Development Goals. This study was conducted to determine the morbidity, mortality and outcomes of children admitted to Gadarif Hospital in eastern Sudan. Method: A retrospective study was conducted by reviewing the medical files of pediatric patients who were admitted to Gadarif Hospital between March 1, 2019 and March 31, 2020. Result: A total of 740 medical files were reviewed. Most, 453 (61.2%) of the admissions were males. The median (interquartile range) age was 3.0 (8.0) years and 433 (58.8%) of the admissions were under five years of age. The median (interquartile range) of the length of hospital stay was 9.0 (12.0) days. Visceral leishmaniasis, malnutrition, severe malaria, sickle cell disease, acute watery diarrhea, severe anemia (regardless of its cause), septicemia and acute respiratory infection were the most common causes of admission. The mortality rate was 5.7%, and it was significantly higher in females than males (24/287 (8.4%) vs. 18/453 (4.0%), P = 0.01) and in children under five years (36/433 (8.3%) vs. 6/307 (2.0%), P < 0.001). Malnutrition, visceral leishmaniasis, septicemia and meningitis/encephalitis were the main diseases causing death in the study population. The case fatality rate was not significantly different in malnutrition than in visceral leishmaniasis (9/93 (9.7%) vs. 7/178 (3.9%), P = 0.05). Conclusion: The main causes of morbidity and mortality for children admitted to Gadarif Pediatric Hospital were communicable diseases. The mortality rate was 5.7%. Females and children under five years were the most vulnerable groups for fatality.